Repetitive Passive Movement Modulates Corticospinal Excitability: Effect of Movement and Rest Cycles and Subject Attention - Tsuiki, Shota; Sasaki, Ryoki; Pham, Manh Van; Miyaguchi, Shota; Kojima, Sho; Saito, Kei; Inukai, Yasuto; Otsuru, Naofumi; Onishi, Hideaki (Frontiers in Behavioral Neuroscience, 2019)
Repetitive passive movement (PM) affects corticospinal excitability; however, it is unknown whether a duty cycle which repeats movement and rest, or subjects’ conscious attention to movements, affects corticospinal excitability. We aimed to clarify the effect of the presence or absence of a duty cycle and subjects’ attention on corticospinal excitability. Three experiments were conducted. In Experiment 1, PM of the right index finger was performed for 10 min. Three conditions were used: 1, continuous passive movement (cPM) at a rate of 40°/s; 2, intermittent passive movement (iPM) with a duty cycle at 40°/s; and 3, iPM at 100°/s. In conditions 1 and 3, motor evoked potential (MEP) amplitude was significantly reduced. In Experiment 2, PM was performed for 30 min: Condition 1 comprised cPM at a rate of 40°/s and Condition 2 comprised iPM at 40°/s. MEP amplitude significantly decreased in both conditions. In Experiment 3, PM was performed for 10 min: Condition 1 comprised paying attention to the moving finger during iPM and Condition 2 was similar to Condition 1 but while counting images on a monitor without looking at the movement finger, and Condition 3 comprised counting images on a monitor without performing PM. MEP amplitude significantly increased only under Condition 1. Thus, afferent input from movements above a certain threshold may affect corticospinal excitability reduction. Furthermore, corticospinal excitability increases when paying attention to passive finger movement.